2007
DOI: 10.1037/0735-7044.121.1.164
|View full text |Cite
|
Sign up to set email alerts
|

The modulation of play fighting in rats: Role of the motor cortex.

Abstract: The cortex is not necessary for rats to engage in play fighting, but it is necessary for them to modify their pattern of play fighting in different contexts. Two experiments were conducted to determine the role of the motor cortex (MC). Rats with bilateral ablations of the MC performed on Postnatal Day 10 failed to show the normally present age-related modulation in defense but were able to modulate defense with different social partners. This latter finding was confirmed in rats given ablations as adults, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 91 publications
(139 reference statements)
2
21
0
Order By: Relevance
“…The PFA, perhaps along with other components of the intralaminar thalamic nuclei, may then be a critical hub in an executive circuit for mammalian playfulness; receiving direct somatosensory input from the spinal cord and sending excitatory projections to areas such as the frontal cortex and striatum (Cesaro et al, 1985;Nakamura et al, 2006;Voorn et al, 2004). As mentioned above, there is evidence for some modulation of play by the prefrontal cortex (Bell, et al, 2009;Kamitakahara, et al, 2007;Pellis, et al, 2006) and the striatum is likely to be important for playful behaviors as well (Gordon et al, 2002;Graham, 2011;) so these areas may help transduce playful somatosensory input into the fluid motor sequences seen during play. Recent evidence suggesting that PFA input to the dorsal striatum facilitates behavioral flexibility (Brown et al, 2010) may be particularly salient in this regard.…”
Section: Neuroanatomical Substrates Of Playmentioning
confidence: 97%
See 1 more Smart Citation
“…The PFA, perhaps along with other components of the intralaminar thalamic nuclei, may then be a critical hub in an executive circuit for mammalian playfulness; receiving direct somatosensory input from the spinal cord and sending excitatory projections to areas such as the frontal cortex and striatum (Cesaro et al, 1985;Nakamura et al, 2006;Voorn et al, 2004). As mentioned above, there is evidence for some modulation of play by the prefrontal cortex (Bell, et al, 2009;Kamitakahara, et al, 2007;Pellis, et al, 2006) and the striatum is likely to be important for playful behaviors as well (Gordon et al, 2002;Graham, 2011;) so these areas may help transduce playful somatosensory input into the fluid motor sequences seen during play. Recent evidence suggesting that PFA input to the dorsal striatum facilitates behavioral flexibility (Brown et al, 2010) may be particularly salient in this regard.…”
Section: Neuroanatomical Substrates Of Playmentioning
confidence: 97%
“…Subsequent studies from Pellis" group found that different areas of the cortex appear to be modulating these different aspects of play. For example, rats with lesions to the motor cortex do not show agerelated changes in play tactics in that males continue to respond predominantly with complete rotations after puberty (Kamitakahara et al, 2007). On the other hand, rats with damage to the orbitofrontal cortex fail to modulate their play based on the status of the partner (Pellis et al, 2006), while rats with damage to the medial prefrontal cortex simply use less complex play tactics (e.g., they are more likely to run away) when solicited (Bell et al, 2009).…”
Section: Neuroanatomical Substrates Of Playmentioning
confidence: 99%
“…Subsequent studies from Pellis’ group found that different areas of the cortex appear to be modulating these different aspects of play. For example, rats with lesions to the motor cortex do not show age-related changes in play tactics in that males respond predominantly with partial rotations before and after puberty (Kamitakahara et al, 2007). On the other hand, rats with damage to the orbitofrontal cortex fail to modulate their play based on the status of the partner (Pellis et al, 2006).…”
Section: Cortical Modulation Of Playmentioning
confidence: 99%
“…The cortex, however, regulates those social aspects of play that allow animals to respond appropriately in specific contexts. Rats with lesions of the primary motor cortex do not exhibit the developmental changes in play behavior characteristic of healthy control animals (Kamitakahara, Monfils, Forgie, Kolb, & Pellis, 2007). Rats with lesions of the orbitofrontal cortex (OFC) fail to modify both their play and non-play behavior with respect to the identity of their social partner (Pellis et al, 2006).…”
mentioning
confidence: 99%